Bio and organomineral fertilization: Nutrient concentrations in the leaf and yield of sugar apple fruits - Leonel, Sarita [UNESP]; Araújo, Jairton Fraga; Tecchio, Marco Antonio [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
Fertilization using organic compounds is a complementary practice to chemical fertilization and strictly necessary to the integrated production of fruits, which is already a reality in almost all European countries. Brazil has tried to adapt its crops to that system, however, there is lack of results in the literature to support recommendations of these techniques to fruit growers. Based on these considerations, the aim of this study was to evaluate the use of natural and organic mineral fertilizers in combination with liquid biofertilizers (ELB= Enriched Liquid Biofertilizer and LB = Leaf Biofertilizer) on the diagnosis of the nutritional status and fruit production of sugar apple. The experiment was carried out in a 9-year old fruit farm of sugar apple with a non-defined cultivar. Spacing was 4 m x 2 m and 1,250 plants ha -1 planting density. A randomized block experimental design was used with four replicates and eight treatments: T1= plants with no fertilization; T2= 60g N; T3= 90 g N; T4= 30g N + 15L ELB + 5% LB; T5= 60g N + 30L ELB + 5% LB; T6= 90g N + 45L ELB + 5% LB; T7= 120g N+ 60L ELB + 5% LB; T8= 150g N + 75g ELB + 5% LB. Plots consisted of 3 plants, amounting to 32 plots and 96 plants. The following variables were analyzed: physical yield per area and mineral composition of leaves in macro and micro nutrients. Treatments 3, 4 and 6 led to yields of 23.6 t ha-1; 21.9 t ha-1 and 23.0 t ha-1, respectively. Mean macronutrient levels were appropriate for the crop, whereas boron, iron, manganese and zing micronutrient levels were inappropriate.
Biofertilização e adubação organomineral: Concentração de nutrientes na folha e produtividade de frutos de pinheira
Keywords: Biofertilizers; Organic manure; Sugar apple fruit; Yield